Labour in Ireland : labour in Irish history : the re-conquest of Ireland - Connoly, James (London : Maunsel and Roberts, 1922)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: arbeidersbeweging; sociale geschiedenis; Ierland